2022
DOI: 10.3390/mi13020309
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Penetration Speed Optimization Based on Intracellular Strain

Abstract: Oocyte penetration is an essential step for many biological technologies, such as animal cloning, embryo microinjection, and intracytoplasmic sperm injection (ICSI). Although the success rate of robotic cell penetration is very high now, the development potential of oocytes after penetration has not been significantly improved compared with manual operation. In this paper, we optimized the oocyte penetration speed based on the intracellular strain. We firstly analyzed the intracellular strain at different pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Additionally, it has been reported that the speed at which the micropipette penetrates cells can have an impact on cell deformation and damage, and optimizing the penetration speed can reduce the damage caused by micropipette penetration to cells [ 25 ]. This inspires the potential improvement of the work in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the speed at which the micropipette penetrates cells can have an impact on cell deformation and damage, and optimizing the penetration speed can reduce the damage caused by micropipette penetration to cells [ 25 ]. This inspires the potential improvement of the work in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Although the success rate of robotic cell penetration is very high, the development potential of oocytes after penetration was not improved significantly compared with manual operations. The authors optimized the oocyte penetration speed based on the intracellular strain [ 11 ]. The authors present a microfluidic system for high-resolution nanoparticle separation based on negative magnetophoresis; this may serve as a versatile tool for separating nanometric objects of environmental or biological importance, such as nanoparticles, viruses, and other biological agents [ 12 ].…”
mentioning
confidence: 99%